La utilización del laboratorio virtual Chemlab para optimizar aprendizajes por descubrimiento de calor del segundo año de bachillerato general unificado (BGU), paralelo H de la unidad educativa Bernardo Valdivieso, sección matutina de la ciudad de Loja, período 2013-2014 - Rosales Aranda, Jessica Elizabeth (2015)
The research topic entitled THE USE OF VIRTUAL LABORATORY ChemLab LEARNING TO OPTIMIZE FOR DISCOVERY OF HEAT THE SECOND YEAR OF BACHELOR OF GENERAL UNIFIED (BGU) H PARALLEL UNIT OF EDUCATIONAL BERNARDO VALDIVIESO, MORNING SECTION OF THE CITY OF LOJA, PERIOD 2013-2014 ; aims to use the virtual lab ChemLab to optimize learning by discovery of Heat students of the Second Year General Unified Baccalaureate (BGU), Parallel Education Unit H Bernardo Valdivieso, morning section of the city of Loja, 2013-2014 ; This paper responds to a descriptive design (diagnosis) and quasi-experimental because it works with a control group; to fulfill the objectives proposed methods as comprehensive, analytic-synthetic, deductive, historical, scientific and quantitative-qualitative who followed the following order is used: understanding, diagnosis, modeling, implementation and assessment of effectiveness, which I have to use diagnostic tools such as surveys on discovery learning heat, pretest, posttest and workshops for implementing virtual laboratory Chemlab; to determine the effectiveness of alternative, we worked with 3 authorities, 32 students, 2 teachers and 10 students from the corresponding educational community of the Education Unit Bernardo Valdivieso, whose results are presented in this thesis. Major findings in this investigation were difficulties, cognitive deficiencies or needs in optimizing heat discovery learning, the same that can reduce or mitigate the use of virtual laboratory Chemlab.